(untitled) (Acta Scientiarum. Health Sciences, 2013)
Previous studies of gait analysis in patients following reconstructive anterior cruciate ligament (ACL) surgery have shown changes in kinematics, kinetics and energy patterns in the lower limb. Usually these patients perform complaint surface training during clinical treatment. The purpose of this study was to evaluate the changes in selected gait kinematic parameters following ACL reconstruction while walking on an unstable surface. We tested 16 subjects: eight patients who underwent ACL reconstruction, at four weeks after the surgical intervention; and eight healthy subjects (control group) matched by age and gender. Participants walked at a self-selected comfortable speed on an 8 m-walkway while sagittal plane kinematic data of the principal lower limb joints (hip, knee and ankle) were collected using 60-Hz cameras. We compared the joint angles under three conditions: (A) walking on stable ground, (B) walking on a foam mat (5 cm thick; 33 kg m-3 density) and (C) back at the normal ground. Results showed that ACL patients were slower and had smaller range of motion at all joints as compared to the control group under all conditions; however the repeated exposure to unstable surface may help changes in such patients. Further investigation is necessary to expand our understanding and may improve the development of more effective rehabilitation treatments.